IMPLEMENTATION OF THE FULFILLMENT OF THE EDUCATIONAL RIGHTS OF FOSTER CHILDREN IN A SPECIAL CHILD DEVELOPMENT INSTITUTION (LPKA) CLASS I BLITAR - Anami, Salmaa Sekar (Journal of Management Small and Medium Enterprises (SMEs), 2025)
According to the Convention on the Rights of the Child and Indonesian law, every child, including those in conflict with the law, is entitled to education, which must be fulfilled even when they are under the care of a Lembaga Pembinaan Khusus Anak (LPKA). However, many children in Indonesia are marginalized from education because of their involvement in crime and admission to LPKA. The government and the children's advocates believe that this is the case when they are given a scholarship to an LPKA. To better understand how education can be optimized for kids under LPKA supervision and what tactics can be used to guarantee that this right is fully realized, this study focuses on the fulfillment of foster children's right to an education at LPKA Class I Blitar. Through documentation studies and interviews, this research employs a case study methodology. Keywords: Fostered Children; Educational Rights; Child Special Development Institution (LPKA)